Distribution and ecological notes on Dynoides (Isopoda: Sphaeromatidae) in the Mexican Pacific - Espinosa-Pérez, María del Carmen; Hendrickx, Michel E (Revista de Biología Tropical, 2002)
Two species of the genus Dynoides Barnard, 1914 (D. crenulatus Carvacho and Haasmann, 1984; D. saldanai Carvacho and Haasmann, 1984) not reported since their description were rediscovered during an intensive sampling program in the intertidal and shallow subtidal of the Mexican Pacific. Both species are abundant in the area and inhabit among the algae Jania adherens Lamouroux, 1816, Amphiroa misakiensis Yendo, 1902, Chaetomorpha linum Kützing, 1845, and Hypnea pannosa Agardh, 1847 from Nayarit to Oaxaca